Prévenir le vol à main armée ? - Poirier, Donate (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
Armed robbery seems to be on the decline in Montreal. But there, as everywhere, prevention is «in». Are there effective ways to prevent armed robbery? To answer this question, the study compared the various means used by a sample of 271 Montreal shop owners : 184 of them had been victims of robbery during the last two years and 87 had as yet never been robbed. There are no easy solutions apart from selling the business. It was found that almost all retailers were prevention conscious. Non-expensive equipment is used in most stores by victims as well as non-victims. Costly means, such as alarms or cameras, are not very common but their preventive effect, if any, could not be other than indirect. Cautious behavior, available to all, seems more effective. Non-victims had adopted slightly more preventive habits than former victims, such as frequent and irregular bank deposits, and/or enhancing the shop's visibility, etc. But so many more factors contribute to crime, several of which are beyond the control of the victim. Prevention also has negative side-effects. Is it worth it?